THE EFFECTS OF PLAYING METHOD TOWARD STUDENTS’ SKILL IN PLAYING MINI VOLLEYBALL - astuti, yuni (LPPM Undiksha, 2018)
Based on the authors observation in the field that there are many students who do not have the skills to play mini volleyball properly. The problem is likely due to the lack of proper training method used. This study aims to reveal the influence of methods on the skills of playing mini volleyball at SD Negeri 14 Kampung Jambak Kecamatan Koto Tangah Padang City. This type of research is a quasi experiment. The population in this study were students who followed extracurricular activities mini volleyball amounted to 64 people, while the sample taken by purposive sampling, so that the sample is amounted to 35 people. The test used is a mini volleyball skill test consisting of service tests, bottom passing and passing up. Data were analyzed using t-test. Results of data analysis found that: play method gives a significant influence on the skills of playing mini volleyball students (t count = 13.01> ttabel = 2.13). The average value of the initial test of the play method was obtained 50.00 and the final test was 63.65. This means there is an increase of 13.65.